Translation strategies and methods of culturemes in the Chinese President’s New Year messages (Orkopata. Revista de Lingüística, Literatura y Arte, 2025)
The objective of this research is to analyze the culturemes present in the Chinese New Year presidential messages delivered between 2023 and 2025, identifying the relationship between their cultural connotations and the choice of translation strategies and methods. The study is grounded in cultural translation theory and applies a corpus-based approach that combines quantitative and qualitative analysis to examine the strategies and methods employed. The findings reveal that culturemes reflect cultural connotations related to a positive attitude and the fundamental values of Chinese society, national colors and subjective states, national identity and spirit, as well as natural landscapes and seasonal concepts. The study concludes that these cultural connotations directly influence the selection of translation strategies and methods, such as foreignization, used to highlight Chinese identity; domestication, which facilitates comprehension; or a combination of both, which balances the two approaches and ensures accurate cultural transmission. Therefore, translators must make decisions based on the different cultural connotations in order to achieve effective communication.
Keywords: culturemes; Chinese President’s speech; translation strategy; translation method; cultural translation